How Accessible are Journal Articles on Education Written by Sub‐Saharan Africa‐based Researchers?. Issue 3 (29th January 2021) - Asare, Samuel; Mitchell, Rafael; Rose, Pauline
ABSTRACT: This article investigates the extent to which education publications authored by researchers based in sub‐Saharan Africa are published as open access (OA). We draw on bibliometric analysis of 1, 858 peer‐reviewed articles over the period 2010‒18, together with interviews with 31 academics based in the region. Overall, we find a steady increase in OA publishing in the region over this period, although the proportion of OA publications remains low. The study finds that: (1) open access articles by researchers in sub‐Saharan Africa are concentrated in journals with a lower impact factor; and (2) authors in sub‐Saharan Africa tend to publish in higher quality journals behind a paywall, rather than in lower quality journals that either have no or lower cost for open access.